Educational and occupational aspirations at the end of secondary school: The importance of regional labour-market conditions - Hartung, Andreas [Verfasser]; Weßling, Katarina [Verfasser]; Hillmert, Steffen [Verfasser] (My University, 2019)
"The transition from general schooling to vocational training or to the labour market marks a crucial threshold in the life course of young adults. It has been well documented that successful school-to-work transitions are influenced by (regional) labour-market conditions. However, what has been rather neglected is that before actual transitions take place, adolescents need to make plans and evaluate their wishes and choices against the background of existing constraints. (Regional) labour-market conditions are a part of such constraints. This paper complements previous research by focusing on the impact of the regional labour market on students' educational and occupational aspirations before school-to-work transitions take place. Regionalised administrative data on unemployment is linked with survey data from the Starting Cohort 4 of the German National Educational Panel Study (NEPS-SC4). Results indicate that a relatively higher level of regional unemployment is associated with aspirations for higher-status occupations. Their status aspiration push students towards continuing general school to obtain higher general qualifications. The effects vary with the attended secondary school track and with parents' educational aspirations for their children." (authors' abstract; BIBB-Doku)
Keywords: P 2.1 Schulabgänger; G 1.3.2.2 Übergänge; G 1.2 Arbeitsmarkt; Schulabgänger; Berufseinmündung; Bildungsaspirationen; Einflussfaktor; Regionaler Arbeitsmarkt